Improvement of CoCr Alloy Characteristics by Ti-Based Carbonitride Coatings Used in Orthopedic Applications; Coatings; Vol. 10, iss. 5 - Dinu M. Mihaela; Pana I. Iulian; Scripca P. Petronela; Sandu I. G. Ioan; Cotrut C. Catalin; Vladesku A. Alina (2020, 2020)
Title screen